Житлово-господарський комплекс рибалок раннього залізного віку на Волині - Козак, Д.Н. (Археологія, 2009)
Висвітлено нові матеріали ранньозалізного часу, отримані при дослідженні багатошарового поселення біля с. Хрінники
на Волині у 2008 р. В 2008 г. при исследовании поселения раннежелезного времени у с. Хринныкы на Ровенщине найдено жилищно-хозяйственный комплекс, который принадлежал профессиональному рыбаку. В комплекс входили: жилище-сушильня и два хозяйственных сооружения. В жилище были лежанка и большая яма посредине, на дне которой размещался глинобитный очаг. По краям ямы обозначены углубления от деревянных конструкций. Видимо, это следы от жердей, на которые навешивалась рыба для сушки или вяления. Под стеной жилищ открыто набор рыбацких снастей, в том числе гарпун, который состоял из трех остов, сложенных в форме тризуба, захват для рыбы, изготовленный из трех икол дикого кабана, и ножа-лопатки для чистки внутренностей рыбы. Находки керамики, бронзовой булавки и других предметов позволяют датировать комплекс VI—V вв. до н. э. In 2008, during the research of the Early Iron Age settlement near Khrinnyky in Rivne region a dwelling and husbandry complex belonging to a professional fisherman was discovered. The complex included a dwelling-drying room and two husbandry buildings. There were a chamber in the dwelling and a large pit in the centre with the cob hearth in the bottom. Along the edges of the pit there were hollows left by the wooden structures. Apparently, these are the traces of poles used for hanging fish for drying or jerking. Under the wall of the dwelling a set of fishing-tackle including harpoon composed of three slings put together in form of a trident, claw for fish composed of three boar fangs, and a knife-shovel for fish viscera cleaning were found. Ceramics, a bronze pin, and other finds allow the author to date the complex by the 6th—5th c. BC.